Isolation and Characterization of Listeria monocytogenes in Selected Food Products - Salih, Midya Bakr; Mohammed, Othman Abdulrahman (Kurdistan Journal of Applied Research, 2025)
Listeria monocytogenes is a significant foodborne pathogen capable of causing severe illness with a high mortality rate, especially in vulnerable populations. Its ability to survive under adverse environmental conditions and contaminate a wide range of foods, including ready-to-eat products, makes it a major public health concern. In Sulaymaniyah and Halabja provinces, there is a lack of systematic data on the prevalence, virulence characteristics, and antimicrobial resistance of L. monocytogenes in locally consumed foods, which limits effective risk assessment and control strategies. This study aimed to determine the prevalence, virulence gene profiles, and antimicrobial resistance patterns of L. monocytogenes in selected dairy, vegetable, and meat products using cultural isolation, biochemical identification, and Polymers Chain Reaction based molecular confirmation. A total of 124 food samples were collected and tested, with molecular detection targeting prs, lmo1030, and 16S rRNA genes, and virulence profiling for hlyA, prfA, and inlA. Antimicrobial susceptibility was assessed against ten antibiotics using the disk diffusion method. Twelve samples (9.6%) were positive for L. monocytogenes, with the highest prevalence in traditional semi-hard cheese (40%), lettuce (25%), and celery (25%). The prfA and inlA genes were each detected in 41.6% of isolates, and hlyA in 33.3%. All isolates were resistant to ampicillin but remained susceptible to most other antibiotics. Thus, these findings provide essential baseline data that can guide targeted food safety interventions and strengthen public health protection measures in this region. Future studies should expand sampling to a wider range of food categories, include seasonal monitoring, and apply whole-genome sequencing to better understand the epidemiology and resistance mechanisms of L. monocytogenes.